Postural imbalance without visual input is associated with specific neuropsychological deficits in older adults – results from the LIFE-adult study - Eva Grill; Andreas Zwergal; Andreas Zwergal; Dorothee Saur; Julian Klingbeil; Christopher Fricke; Florian Schöberl; Karim Felfela; Karim Felfela; Andrea Zülke; Steffi Riedel-Heller; Joseph Classen (Frontiers in Neurology)
IntroductionModifiable risk factors play an important role in preventing dementia and reducing its progression. Regular physical activity already in midlife, which relies on intact multisensory balance control, can help to decrease the risk of dementia. However, our understanding of the relationship between postural balance and cognitive functions remains limited. The objective of our study was to investigate the association of postural balance during different sensory conditions with specific cognitive domains in older adults.MethodsParticipants were from the population-based prospective “Leipzig Research Center for Civilization Diseases” (LIFE-Adult) cohort in Leipzig, Germany. Executive, memory and processing speed functions were tested by the Consortium to Establish a Registry for Alzheimer’s disease (CERAD) plus battery. Assessment of visuospatial abilities was based on the short form of the Judgment of Line Orientation Test (JLO). Postural sway was recorded on a force plate with eyes open and closed. Romberg’s ratios were calculated for sway path and sway area as a proxy for balance without visual control and tested in generalized linear regression models with the summary scores of executive function, memory, processing speed and visuospatial function as dependent variables. All models were adjusted for sex, age, ApoE status, socioeconomic status, anamnestic stroke, and diabetes.ResultsIn total, we analyzed 460 participants with a mean age of 68.6 years, range 60 to 80, 47.6% female. A higher Romberg’s ratio for sway area was a significant indicator for impaired visuospatial abilities as measured by the dichotomized JLO (Odds Ratio = 1.42, 95% confidence interval 1.07 to 1.88). Romberg’s ratios were not significantly associated with executive functions, procedural speed or memory functions.DiscussionIt may be worthwhile to examine in the future whether inclusion of balance testing enhances the value of screening programs for cognitive impairment. Inversely, it may be appropriate to apply routine cognitive tests when balance problems are detected in older patients.